Human papilloma virus genotyping for the cross‐sectional and longitudinal probability of developing cervical intraepithelial neoplasia grade 2 or more. Issue 2 (9th March 2018) - Del Mistro, Annarosa; Adcock, Rachael; Carozzi, Francesca; Gillio‐Tos, Anna; De Marco, Laura; Girlando, Salvatore; Rizzolo, Raffaella; Frayle, Helena; Trevisan, Morena; Sani, Cristina; Burroni, Elena; Giorgi Rossi, Paolo; et al.
Abstract : Human papilloma virus (HPV) testing is more sensitive but less specific than cytology. We evaluated stand‐alone genotyping as a possible triage method. During a multicentre randomised controlled trial comparing HPV testing to conventional cytology, HPV‐positive women were referred to colposcopy and followed up if no high‐grade lesion was detected. HPV‐positive samples were genotyped by GP5+/GP6+ primed polymerase chain reaction followed by reverse line blot. Genotypes were hierarchically ordered by positive predictive value (PPV) for CIN grade 2 or more (CIN2+), and grouped by cluster analysis into three groups (A, B and C in decreasing order). Receiver operating characteristic curves were computed. Among 2, 255 HPV‐positive women with genotyping, 239 CIN2+ (including 113 CIN3+) were detected at baseline or during a 3‐year follow‐up. HPV33 had the highest PPV with CIN2+ and CIN3+ as the endpoint and when considering lesions detected at baseline or also during follow‐up. HPV16 and HPV35 were the second and third, respectively. Cross‐sectional sensitivity for CIN2+ at baseline was 67.3% (95% CI 59.7–74.2), 91.8% (95% CI 86.6–95.5) and 94.7% (95% CI 90.2–97.6), respectively, when considering as "positive" any of the HPV types in group A (33, 16 and 35), A or B (31, 52, 18, 59 and 58) and A or B or C (39, 51, 56, 45 and 68). The corresponding cross‐sectional PPVs for CIN2+ were 15.8% 95% (CI 13.2–18.7), 12.0% (95% CI 10.3–13.9) and 9.6% (95% CI 8.2–11.1), respectively. HPV33, 16 and 35 confer a high probability of CIN2+ but this rapidly decreases when adding other genotypes. Abstract : What's new? The Human papilloma virus (HPV) infection genotype is an early predictor of cervical lesions. The current focus lies on high‐risk genotypes 16 and 18, frequently found in cancers. Here the authors studied the predictive value of all carcinogenic types and identified infections with HPV16, but also HPV33 and 35, as conferring very high risk for the development of high‐grade cervical intraepithelial neoplasia (CIN2+). However, HPV genotyping alone did not reliably triage women, and combinations with other methods are recommended.